2011
DOI: 10.2298/ntrp1103254v
|View full text |Cite
|
Sign up to set email alerts
|

Simulated radiation effects in the superinsulating phase of titanium nitride films

Abstract: This paper investigates possible effects of alpha particle and ion beam irradiation on the properties of the superinsulating phase, recently observed in titanium nitride films, by using numerical simulation of particle transport. Unique physical properties of the superinsulating state are considered by relying on a two-dimensional Josephson junction array as a model of material structure. It is suggested that radiation-induced change of the Josephson junction charging energy would not affect the current-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…There has been no ticed a large number of metal at oms (Ti, Zr, Hf, Sr, Ga) dis place ments through out the ox ide. Pri mary dis placed metal and ox ygen at oms cause fur ther dis place ments that can produce a dis place ment tree [17,18]. Pri mary knock-on at oms with en ergy less than 2 keV re sult in iso lated defects.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no ticed a large number of metal at oms (Ti, Zr, Hf, Sr, Ga) dis place ments through out the ox ide. Pri mary dis placed metal and ox ygen at oms cause fur ther dis place ments that can produce a dis place ment tree [17,18]. Pri mary knock-on at oms with en ergy less than 2 keV re sult in iso lated defects.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these lim i ta tions, sev eral ex per i ments have been re ported at very low tem per a tures (15-40 K), val i dat ing the TRIM re sults [21]. Also, TRIM has been suc cess fully used for sim ula tions of ra di a tion ef fects in var i ous kinds of mem ory cells and com po nents [8][9][10]22].…”
Section: Sim U La Tion and Cal Cu La Tion Meth Odsmentioning
confidence: 99%
“…Pre vi ous cal cu la tions of the pro ton dose and absorbed dose from ion beams in mem ory com po nents mostly used, have now a days shown that there are ir radi a tion con di tions and dose lev els for ev ery type of mem ory cell when ra di a tion-in duced changes of charac ter is tics and func tion al ity of these cells should be ex pected [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous years it has been practice that simulations of radiation effects and assesment of dose ranges in which these effects are expected should be conducted before costly and time consuming component irradiations at accelerating facilities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%